Variation in the Thermal Parameters of Odontophrynus occidentalis in the Monte Desert, Argentina: Response to the Environmental Constraints - Sanabria, Eduardo Alfredo (2012)
We studied the variation of thermal parameters of Odontophrynus occidentalis between season (wet and dry) in the Monte desert (Argentina). We measured body temperatures, microhabitat temperatures, and operative temperatures; while in the laboratory, we measured the selected body temperatures. Our results show a change in the thermal parameters of O. occidentalis that is related to environmental constraints of their thermal niche. Environmental thermal constraints are present in both seasons (dry and wet), showing variations in thermal parameters studied. Apparently imposed environmental restrictions, the toads in nature always show body temperatures below the set point. Acclimatization is an advantage for toads because it allows them to bring more frequent body temperatures to the set point. The selected body temperature has seasonal intraindividual variability. These variations can be due to thermo-sensitivity of toads and life histories of individuals that limits their allocation and acquisition of resources. Possibly the range of variation found in selected body temperature is a consequence of the thermal environmental variation along the year. These variations of thermal parameters are commonly found in deserts and thermal bodies of nocturnal ectotherms. The plasticity of selected body temperature allows O. occidentales to have longer periods of activity for foraging and reproduction, while maintaining reasonable high performance at different temperatures. The plasticity in seasonal variation of the thermal parameters has been poorly studied, and is greatly advantageous to desert species during changes in both seasonal and daily temperature, as these environments are known for their high environmental variability.